Novel concrete superplasticizers based on phosphate esters. (May 2019) - Stecher, J.; Plank, J.
Abstract: Novel polyphosphate superplasticizers were synthesized by copolymerization reaction between 2-(methacryloyl oxy) ethyl phosphate monomer and the macromonomer polyethylene glycol methacrylate ester at different molar ratios. The synthesized phosphated comb polymers were characterized by size exclusion chromatography and elemental analysis and their dispersing performance in cement was assessed via mini slump tests in cement paste. The phosphated comb polymers exhibited superior dispersing performance over conventional polycarboxylate comb polymers (PCEs), were less retarding on cement and showed comparable robustness against sulfate and clay impurities. These properties can be explained by the high calcium complexing capacity of the phosphate groups. Thus, phosphated comb polymers present a viable alternative to polycarboxylate superplasticizers.